Competition law and access to medicines: Lessons from Brazilian regulation and practice - Matheus Z. Falc\~ao; Mariana Gondo; Ana Carolina Navarrete (South Centre, 2022)
Competition law may play an important role in drug pricing control by containing high prices derived from economic violations. Since the use of competition tools is not limited by the TRIPS Agreement or other international binding disciplines, there is ample policy room to explore how countries, especially in the Global South, can benefit from strengthening their jurisdiction on that matter. This article briefly explains the Brazilian Competition System by describing the structure of the Brazilian competition authority (CADE - Administrative Council for Economic Defense) and the main economic violations set forth by Brazilian law. It describes the convergence of competition with the consumer protection system. It also discusses three relevant pharmaceutical market cases examined by the competition authority (sham litigation, overpricing and economic abuse, buy-and-raise and exclusionary practices). Finally, it presents some lessons from the Brazilian case on the challenges of using competition law to confront abuse or misuse of intellectual property rights in the pharmaceutical market, with lessons to other developing countries.
Keywords: 300; Wettbewerbsrecht; Preisregulierung; Immaterialgüterrechte; Arzneimittelmarkt; Gesundheitsversorgung; Arzneimittel; Brasilien